Functional Muscle Transfer after Oncologic Extremity Resection - Hassan, Abbas M.; Tesfaye, Eliora A.; Rashiwala, Abhi; Roubaud, Margaret J.; Mericli, Alexander F. (Journal of Reconstructive Microsurgery, 2022)
Background Functional muscle transfer (FMT) can provide wound closure and restore adequate muscle function for patients with oncologic extremity defects. Herein we describe our institutional experience with FMT after oncological resection and provide a systematic review and meta-analysis of the available literature on this uncommon procedure.Methods A single-institution retrospective review was performed, including all patients who received FMT after oncological resection from 2005 to 2021. For the systematic review and meta-analysis, PubMed, Cochrane, Medline, and Embase libraries were queried according to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines; results were pooled, weighted by study size, and analyzed.Results The meta-analysis consisted of seven studies with 70 patients overall, demonstrating a mean Medical Research Council (MRC) score of 3.78 (95% confidence interval: 2.97–4.56; p < 0.01). The systematic review included 28 studies with 103 patients. Receipt of adjuvant chemotherapy was associated with significantly lower mean MRC score (3.00 ± 1.35 vs. 3.90 ± 1.36; p = 0.019). Seventy-four percent of the patients underwent free FMT, with the most common donor muscle being the latissimus dorsi (55%). The flap loss rate was 0.8%. Neoadjuvant chemotherapy (p = 0.03), radiotherapy (p = 0.05), pedicled FMTs (p = 0.01), and a recipient femoral nerve (p = 0.02) were associated with significantly higher complication rates. The institutional retrospective review identified 13 patients who underwent FMT after oncological resection with a median follow-up time of 21 months (range: 6–74 months). The most common tumor necessitating FMT was undifferentiated pleomorphic sarcoma (77%), and the most common donor muscle was the latissimus dorsi (62%). A high body mass index was associated with prolonged neuromuscular recovery (R = 0.87, p = 0.002).Conclusion FMT after oncological resection may contribute to improved extremity function. Careful consideration of risk factors and preoperative planning is imperative for successful FMT outcomes.
Keywords: flaps; surgical; soft-tissue sarcoma; functional muscle transfer